Breast cancer survivors suffer from persistent postmastectomy pain syndrome and posttraumatic stress disorder (ORTHUS study): a study of the palliative care working committee of the Turkish Oncology Group (TOG) - (:unkn) unknown (SPRINGER, 2016)
Persistent postmastectomy pain syndrome (PMPS) is one of the most important disturbing symptoms. Posttraumatic stress disorder (PTSD) is an anxiety disorder which is characterized by reactions to reminders of the trauma that has been experienced. The purpose of this study is to evaluate the predictors of PMPS and PTSD in Turkish breast cancer survivors and the correlation between PMPS and PTSD. The study is designed as a multicenter survey study. Breast cancer patients in remission were evaluated. Patients were evaluated with structured questionnaires to assess the PMPS and clinical parameters associated with it. The Turkish version of the posttraumatic stress disorder checklist-civilian version (PCL-C) was used. Between February 2015 and October 2015, 614 breast cancer survivors in outpatient clinics were evaluated. The incidence of PMPS documented is 45.1 %. In the multivariate analysis low income, presence of PTSD and < 46 months after surgery were associated with increased risk of PMPS. PTSD was documented in 75 %, and the mean PCL-C score was 32.4 +/- 11.1. PMPS and being married at the time of the evaluation were linked with PTSD. It is the first data about the association between PMPS and PTSD. The clinicians should be aware of PMPS and PTSD in breast cancer survivors.
Keywords: Breast cancer survivor; Persistent postmastectomy pain syndrome; Posttraumatic stress disorder; BONE-MARROW-TRANSPLANTATION; QUALITY-OF-LIFE; RISK-FACTORS; NEUROPATHIC PAIN; FOLLOW-UP; SURGERY; PREVALENCE; SYMPTOMS; PTSD; SYMPTOMATOLOGY